2022
DOI: 10.1002/ctm2.954
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rescue ameliorates mitochondrial encephalo‐cardiomyopathy in murine and human iPSC models of Leigh syndrome

Abstract: Background Mice with deletion of complex I subunit Ndufs4 develop mitochondrial encephalomyopathy resembling Leigh syndrome (LS). The metabolic derangement and underlying mechanisms of cardio‐encephalomyopathy in LS remains incompletely understood. Methods We performed echocardiography, electrophysiology, confocal microscopy, metabolic and molecular/morphometric analysis of the mice lacking Ndufs4. HEK293 cells, human iPS cells‐derived cardiomyocytes and neurons were us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The NAD + /NADH ratio is essential to maintaining redox balance of the cell, and reduced concentrations of NAD are linked to poor metabolic health in aging and chronic diseases [ 21 , 22 ]. Elevating NAD levels by targeted supplementation has improved health and reversed pathology in animal models of disease [ 23 , 24 ], and NAD enhancing supplements are currently being tested in clinical trials for multiple human conditions [ 25 , 26 , 27 ]. The therapeutic use of NAD+ precursors, such as nicotinamide riboside (NR), as a therapeutic target to compensate for deficits in complex I, is particularly appealing in PD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NAD + /NADH ratio is essential to maintaining redox balance of the cell, and reduced concentrations of NAD are linked to poor metabolic health in aging and chronic diseases [ 21 , 22 ]. Elevating NAD levels by targeted supplementation has improved health and reversed pathology in animal models of disease [ 23 , 24 ], and NAD enhancing supplements are currently being tested in clinical trials for multiple human conditions [ 25 , 26 , 27 ]. The therapeutic use of NAD+ precursors, such as nicotinamide riboside (NR), as a therapeutic target to compensate for deficits in complex I, is particularly appealing in PD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…To examine the role of microglia in LS encephalopathy, we used LS mouse model with Ndufs4 −/− , which developed multiple brain lesions, particularly in the brainstem and cerebellum, associated with increase in microglia (Quintana et al, 2010 ; Yoon et al, 2022 ). We showed that partial ablation of microglia by Pexidartinib may confer protective effect and extend lifespan of Ndufs4 −/− mice, but only when it was administered approximately at the onset of neurological symptoms during which activated microglia has been documented (Quintana et al, 2010 ; Aguilar et al, 2022 ; Yoon et al, 2022 ) (late Pexi, Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the role of microglia in LS encephalopathy, we used LS mouse model with Ndufs4 −/− , which developed multiple brain lesions, particularly in the brainstem and cerebellum, associated with increase in microglia (Quintana et al, 2010 ; Yoon et al, 2022 ). We showed that partial ablation of microglia by Pexidartinib may confer protective effect and extend lifespan of Ndufs4 −/− mice, but only when it was administered approximately at the onset of neurological symptoms during which activated microglia has been documented (Quintana et al, 2010 ; Aguilar et al, 2022 ; Yoon et al, 2022 ) (late Pexi, Figure 3 ). A plausible explanation for the detrimental effects of early Pexi in depleting microglia is that microglia play critical physiological roles in phagocytosis of cellular debris, secretion of signaling molecules (e.g., neurotrophins) and essential homeostasis during CNS development, maturation and in diseased state (Anderson and Vetter, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying its pathogenesis are not fully understood and no therapies are approved for the treatment of patients with LS. In a new study, Yoon and colleagues 1 shed light on the pathophysiological mechanisms of cardio‐encephalomyopathy in LS and demonstrates that nicotiname riboside (NR) provides significant amelioration in disease models of LS (Figure 1).…”
Section: Figurementioning
confidence: 99%